Meningkatkan Pengendalian Emosi Tunalaras Melalui Film “Jalan Pulang” Di BRSBKL Yogyakarta - Alaudin Ghaly Argyanto; Daratul Baidah; Putri arum Sari; Gudang Budiman; Muhammad Syahrul Fadilah; Fiza Nafisatun Najah (CV. ITTC INDONESIA, 2025)
This research aims to improve emotional control of the mentally retarded through showing the film